Web-Base Help Desk System for Telecenter - Glood, Salih H. (2009)
Help Desk System is an integral part of many organizations that must support products or services. In the complex help desk environment, analysts with varying skill levels rely on their expertise as well as systems, tools, and repositories to answer a range of problems.Telecentre (TC) often needs support to address problems faced in their daily routine, and it is expensive to call or ask for visits from the stakeholders. Hence, the study will propose a web based Help Desk System for the telecentre to provide administrator with the appropriate details relevant to their requirements. The study will follow the Spiral development model.